Termitophile encounter may be costly to the termite host - Carvalho, Yuri Carvalho de (2018)
Termites nests are commonly invaded by other arthropods looking for food or shelter. These invaders cohabit with the builder species forming a symbiotic association known as termitophily. As every interespecific in- teraction, symbioses are characterized in a cost-benefit perspective, which defines if the interaction is positive or negative to the species associated. However, for termitophily, such costs and benefits are still poorly unders- tood, specially because it occurs cryptically, with the closed environment of a termitarium. Given this gap in the study of termitophily, in this dis- sertation we measured the costs arisen from the interespecific encounters between the termite Constrictotermes cyphergaster Silvestri 1901 (Termitidae: Nasutitermitinae) and the termitophilous beetle Corotoca melantho Schiødte 1853 (Staphylinidae: Aleocharinae), using a parameter of survival of individuals when confined in interspecific groups. To investigate what could cause such costs, we performed behavioral observations of the termitophile with its host termite in laboratory bioassays. Because termites on labora- tory bioassays would be exposed to an illumination they do not experience naturally, we additionally check the effects of cold white lights and infrared lights on termites survival. The results showed that the termitophile presence was costly to termites, reducing their survival, while the termite presence was beneficial to the beetles delaying their time until death. Additionally, as termitophile numbers decreased, we observed that termites survival increased. These results seem to stem from negative effects of the termitophiles upon termites. In mixed-species groups, termitophiles were shown to engage in mouth-to-mouth contacts with termites, and to fre- quently bite their hosts; such interactions resulting in significant reduction in termite survival. These effects were progressively stronger as the proportion of C. melantho individuals relative to their termite host increased. Very harmfull effects, however, would be only observed in C. melantho propor- tions far above the values normally observed in the field. It seems hence that termitophiles natural low abundance inside termitaria would make their costs unnoticed by their host termites. Regarding the illumination on the bioassays, when comparing survival of termites exposed to artificial lights with those kept in the dark, no statiscal difference was found. We then propose that bioassays can be conducted under infrared or cold white light as these light regimes do not affect the survival of tested individuals.